Pengembangan Paket Modul Cetak Mata Pelajaran Pendidikan Agama Islam (PAI) untuk Siswa SMA Negeri 1 Wangi-wangi Kabupaten Wakatobi - Westomi, Joko Azis; Ibrahim, Nurdin; Sukardjo, Moch (JTP - Jurnal Teknologi Pendidikan, 2018)
The purpose of this research and development is to produce a package of Islamic religious education print modules, to determine the feasibility of a package of Islamic religious education print modules, and to find out the effectiveness of the Islamic religious education print module package. Modules are used for selfdirected and conventional learning. The research method used is the development method. This study uses the Rowntree development model consisting of three stages of preparation, namely the planning stage, the preparation stage of writing, and the writing and editing stages. Testing the product done to the material experts showed the average score of 4.66 means that the product is considered good, and media experts of 4.79 means the product is considered very good, to students, ie 3 students for the stage face to face with the results of the average score the average of 3.30 means that the product is considered good, and 30 students for the field trial evaluation stage of 4.31 means that the product is considered very good. In conclusion the product can already be said to be good but still there needs to be some improvement in accordance with expert advice, students, and teachers.